A REVIEW: FILM FORMING GEL NOVEL DRUG DELIVERY SYSTEM - Bornare, Swapnil S.; Aher, Smita S.; Saudagar, Ravindranath B. (International Journal of Current Pharmaceutical Research, 2018)
Film forming gels are a novel approach in this area that might present an alternative to the conventional dosage forms used on the skin, such as ointments, creams, gels or patches. The polymeric solution is applied to the skin as a liquid and forms an almost invisible film in situ by solvent evaporation. Transdermal drug delivery system (TDDS) and dermal drug delivery system can provide some desirable performances over conventional pharmaceutical dosage formulations, such as avoiding gut and hepatic first-pass metabolism, improving drug bioavailability, reducing dose frequency and stabilizing drug delivery profiles. The aim of this review was to search for alternatives to the conventional forms in order to reduce skin irritation, improve skin adhesion properties, enhance the drug release and increase the patient acceptability from an aesthetic perspective. Because of their peculiar rheological behaviour, polymeric gels are beneficial in terms of ease of preparation, ease of application, adhesion to the application surface and ability to deliver a wide variety of drugs.